(untitled) (Research, Society and Development, 2020)
The objective was to develop vegetarian recipes that could be prepared on a large scale, to be included in the menu of the University Restaurant (RU) of the State University of Rio de Janeiro. Searches for vegetarian recipes were carried out on books and cooking websites. Twenty-two culinary recipes possibly applicable on a large scale and meeting the criteria of the RU term of reference were selected. Of these, only six met the eligibility criteria and were selected for testing in a culinary laboratory, for cost analysis and their suitability for the nutritional parameters of the Worker Food Program (PAT, in Brazil). The cost of the recipes was considered acceptable (R 0.38 to R 0.99 per serving). Most of the menus containing the selected recipes showed inadequate energy values and the amounts of carbohydrate, protein, saturated fat and sodium were above the parameters established by PAT. The chickpea burger with cauliflower sauce was prepared at the RU facilities and evaluated through an affective test by users who agreed to participate in the study and who signed the Free and Informed Consent Form. More than half (57.6%) of the users liked the appearance, while 48.5% and 42.4% appreciated the flavor and consistency, respectively. The recipes selected after the adaptations were considered well accepted and applicable on a large scale, demonstrating the possibility of their inclusion in the RU menu. Although well accepted, some need modifications to improve nutritional parameters and cost.